2007
DOI: 10.1177/1934578x0700201207
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Insecticidal Effect and Repellent Activity of Essential Oils of Three Aromatic Plants, Alone and in Combination, towards Sitophilus Oryzae L. (Coleoptera: Curculionidae)

Abstract: Essential oils of aromatic plants with insecticidal properties are nowadays considered as alternative insecticides to protect stored products from attack by insect pests. A combination of some of these plants in the granaries is a current practice in certain localities of northern Cameroon. The aim of the present work was to analyze the impact of the combinations of the essential oils of Vepris heterophylla (Rutaceae), Ocimum canum, and Hyptis spicigera (both Lamiaceae), the three most used local aromatic plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Linalool (Figure B, 44.13%), eugenol (17.68%), and 1,8‐cineole (10.19%) were the major components followed by terpinen‐4‐ol (4.83%) and α‐ trans‐ bergamotene (2.94%). Previous investigations on the chemistry of the essential oil of O. canum have shown the presence of several chemotypes, namely, limonene‐rich (Ngassoum and others ; Ngassoum and others ), 1,8‐cineole rich (Bassole and others ), camphor‐rich (Upadhyay and others ; Chagonda and others ), linalool‐rich (Ngassoum and others ), α‐terpineol‐rich, chavicol‐ and α‐terpineol‐rich (Chalchat and others ), and methyl trans‐cinnamate‐rich chemotypes (Martins and others ). The present chemotype, described in this study, has a similar composition with those of the North Cameroon type reported by Ngassoum and others () wherein the oxygenated monoterpenoids were the major components (91.9%) with linalool at 44.9%, as one of the main constituents.…”
Section: Resultsmentioning
confidence: 98%
“…Linalool (Figure B, 44.13%), eugenol (17.68%), and 1,8‐cineole (10.19%) were the major components followed by terpinen‐4‐ol (4.83%) and α‐ trans‐ bergamotene (2.94%). Previous investigations on the chemistry of the essential oil of O. canum have shown the presence of several chemotypes, namely, limonene‐rich (Ngassoum and others ; Ngassoum and others ), 1,8‐cineole rich (Bassole and others ), camphor‐rich (Upadhyay and others ; Chagonda and others ), linalool‐rich (Ngassoum and others ), α‐terpineol‐rich, chavicol‐ and α‐terpineol‐rich (Chalchat and others ), and methyl trans‐cinnamate‐rich chemotypes (Martins and others ). The present chemotype, described in this study, has a similar composition with those of the North Cameroon type reported by Ngassoum and others () wherein the oxygenated monoterpenoids were the major components (91.9%) with linalool at 44.9%, as one of the main constituents.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, formulation of EOs with other compounds, as well as formulations of different EOs, may enhance repellent ability by synergistic activity of the components. For instance, Ngassoum et al [119] proved that Ocimum canum (Lamiaceae) could improve the repellence of Hyptis spicigera (Lamiaceae) EO against S. oryzae, conversely to Vepris heterophylla (Rutaceae) which caused an antagonistic effect. e characteristic of EOs to act as antifeedant compounds is a key repellent mechanism, with a number of perspectives under operative conditions.…”
Section: Repellent Activitymentioning
confidence: 99%
“…Essential oils are a rich source of biologically active compounds and generally possess a strong and persistent odour, usually characteristic of the plant in which they are found. Essential oils have been shown to possess in‐vitro antibacterial, antifungal, antioxidant, analgesic, anti‐inflammatory, insecticidal and antiviral properties [1–3] . Some components of essential oils have also been shown to exert both in‐vitro and in‐vivo anti‐tumour activity against murine leukaemia, hepatoma and melanoma cells.…”
Section: Introductionmentioning
confidence: 99%